ANALYSIS OF CONGENITAL ANOMALY TRENDS AND IMPLICATIONS IN A TERTIARY CARE HOSPITAL: A STUDY FROM PESHAWAR, PAKISTAN - SYED , W; LIAQAT , N; RAFIQ , S; HASSAN , N; ABID , F (Biological and Clinical Sciences Research Journal, 2023)
This research, conducted at a tertiary care hospital in Peshawar, Pakistan, aimed to examine the trends and rates of congenital malformations. The study was a cross-sectional study that took place from January 2021 to January 2022 at the Department of Gynaecology & OBs MTI, LRH Peshawar. The study's objectives were to determine the frequency and trends of congenital disabilities in infants, identify risk factors associated with these conditions, and suggest prevention and early intervention measures. The study excluded stillbirths but included newborns with congenital disabilities diagnosed through clinical examinations such as chromosomal analysis, radiography, and ultrasound. Information on kinship, maternal and prenatal history, and other risk factors were gathered through records and interviews. Statistical analysis was conducted using Fisher's exact test and chi-square test. The most common congenital anomaly identified was musculoskeletal abnormalities, accounting for 3.8% of cases. The study highlights the importance of prenatal diagnosis and treatment for prevention and timely intervention. The study's limitations include its hospital-based setting and exclusion of stillbirths, which may have led to an underestimation of prevalence. Nonetheless, the research sheds light on the need for early detection and prevention of congenital anomalies and associated risk factors. According to the report, congenital abnormalities affect 3.8% of babies at Lady Reading Hospital in Peshawar. Consanguinity and fetal abnormalities were significantly correlated (p<0.05). Five occurrences of anencephaly were reported, making central nervous system (CNS) abnormalities the most common kind. Gastrointestinal tract (GIT) abnormalities accounted for 15% of cases, whereas musculoskeletal anomalies accounted for 33.2%. The genitourinary (10.5%), cardiovascular (9.1%), and cutaneous (8.7%) systems were also impacted. Although these results are consistent with other studies, if abortions and stillbirths had been taken into account, the frequency may have been greater. Prenatal diagnosis and early antenatal care are essential for intervention and prevention. The analysis shows that congenital abnormalities were 3.8% common throughout the study period at Lady Reading Hospital in Peshawar. Fetal abnormalities were substantially correlated with consanguinity. Anomalies in the central nervous system showed the most significant occurrence. Prenatal diagnosis and early antenatal care are crucial for intervention and prevention.